Combination of Coprecipitation and Sonochemical Methods in Synthesizing Spinel Hausmannite Nanomaterial - Nurul Hidayat; Ahmad Taufiq; Sunaryono Sunaryono; Samsul Hidayat; Heriyanto Heriyanto; Era Budi Prayekti (Universitas Negeri Surabaya, 2018)
As it has been widely known that the spectacular characteristics of nanomaterials are strongly dependent on their particle size, crystal structure, and molecular arrangement. The fine structure formation of nanomaterials is inevitable in an attempt of optimizing their promising applications in various fields. One of the notable nanomaterials up to now is hausmannite or Mn3O4. This paper presents a combination of coprecipitation and sonochemical routes in a concurrent way to produce spinel-structured hausmannite nanomaterials. The pH was varied during the synthesis at values of 9, 10, 11, 11.5, and 12. The crystal structure properties were evaluated by X-ray diffractometry (XRD) with the diffraction angle range of 15° - 80°. The functional groups were investigated by Fourier transform infrared (FTIR) spectrometry having wavenumber from 400 to 4000 cm-1. In this study, pH 10 was found to be the best synthesis parameter in producing Mn3O4. Both XRD and FTIR data analyses have agreed on the formation of spinel hausmannite nanomaterials.